2022
DOI: 10.1097/icl.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Keratitis Associated With Penetrating Keratoplasty and Scleral Lens Wear: A Case Series

Abstract: Objectives:To report on microbial keratitis (MK) in three scleral lens (SL) wearers who had undergone penetrating keratoplasty (PKP).Methods:This retrospective case series describes 3 cases of MK in patients who wore SLs after PKP.Results:All three patients wore SLs for visual rehabilitation for corneal irregularity induced by PKP; all three also had concurrent ocular surface disease (keratoconjunctivitis sicca and corneal exposure). Cultures identified the causative organism in two patients, and septated hyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…16 Scleral lenses may also be associated with a high risk of infectious keratitis compared to other types of contact lenses with reports between 0.5-1.6%. [17][18][19][20] Kawulok et al reported on three patients that microbial keratitis associated with scleral lens wear and penetrating keratoplasty. 17 Of the nine patients in our case series, seven patients wore scleral contact lenses, which suggests that this type of lens may be associated with risks of developing contact-lens-associated infectious keratitis, but comparative studies are needed to prove that theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Scleral lenses may also be associated with a high risk of infectious keratitis compared to other types of contact lenses with reports between 0.5-1.6%. [17][18][19][20] Kawulok et al reported on three patients that microbial keratitis associated with scleral lens wear and penetrating keratoplasty. 17 Of the nine patients in our case series, seven patients wore scleral contact lenses, which suggests that this type of lens may be associated with risks of developing contact-lens-associated infectious keratitis, but comparative studies are needed to prove that theory.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Kawulok et al reported on three patients that microbial keratitis associated with scleral lens wear and penetrating keratoplasty. 17 Of the nine patients in our case series, seven patients wore scleral contact lenses, which suggests that this type of lens may be associated with risks of developing contact-lens-associated infectious keratitis, but comparative studies are needed to prove that theory. In addition, the prevalence of microbial keratitis after penetrating keratoplasty without the use of contact lens has been reported as between 1.8% and 12.1%.…”
Section: Discussionmentioning
confidence: 99%
“…1 Visual and physiologic benefits of wearing SLs have been described, 2 but risks of corneal complications associated with SL wear are less clearly defined. Isolated case reports 3,4 and retrospective reviews 5,6 have described microbial keratitis (MK) in SL wearers. Other corneal complications such as perilimbal corneal epithelial bullae, 7 transient epithelial bullae, 8 and corneal endothe-lial blebs 9 have also been reported.…”
mentioning
confidence: 99%